Pengaruh Konsentrasi NaBH4 dan Penambahan Surfaktan Sodium Dodecyl Sulfate (SDS) dalam Sintesis Nanopartikel Perak sebagai Material Antibakteri - Arif Budianto Cuaca; Ratna Frida Susanti; Anastasia Prima Kristijarti; Widi Astuti; Himawan Tri Bayu Murti Petrus; Wanta, Kevin Cleary (Jurnal Rekayasa Proses, 2024)
This study was carried out to study the synthesis of silver nanoparticles in which the concentrations of the reducing agent NaBH4 and SDS surfactant varied. Furthermore, the silver nanoparticles formed were characterized and tested for their antibacterial capabilities to show how varying parameters could influence the properties of silver nanoparticles as an antibacterial material. 0.05 M AgNO3 precursor solution was mixed with NaBH4 solution as a reducing agent in the 0.001–0.015 M concentration range. In addition, surfactant was also added under CMC conditions. The Ag+ ion reduction process took place at room temperature for 5 minutes. Then, the colloidal silver nanoparticle samples were characterized and tested for antibacterial properties. The bacteria used are Escherichia coli and Staphylococcus aureus. This study reduced 98% of Ag+ ions to Ago particles when using surfactants and the highest concentration of NaBH4, whereas the synthesis of silver nanoparticles without surfactants could only reduce 88% of Ag+ ions. Using surfactants also produces particles with a much smaller diameter, around 51 nm. Antimicrobial testing also showed that silver nanoparticles with surfactants could inhibit bacterial growth. Thus, using surfactants and high concentrations of NaBH4 can provide better antimicrobial characteristics and capabilities to these silver nanoparticles.